The Development of a Juvenile Porcine Augmented Renal Clearance Model Through Continuous Infusion of Lipopolysaccharides: An Exploratory Study - Dhondt, Laura; Croubels, Siska; Temmerman, Robin; De Cock, Pieter; Meyer, Evelyne; Van Den Broeck, Wim; De Paepe, Peter; Devreese, Mathias (Frontiers in Veterinary Science, 2021)
Augmented renal clearance (ARC) as observed in the critically ill (pediatric) population can have a major impact on the pharmacokinetics and posology of renally excreted drugs. Although sepsis has been described as a major trigger in the development of ARC in human critically ill patients, mechanistic insights on ARC are currently lacking. An appropriate ARC animal model could contribute to reveal these underlying mechanisms. In this exploratory study, a state of ARC was induced in 8-week-old piglets. Conscious piglets were continuously infused over 36 h with lipopolysaccharides (LPS) from Escherichia coli (O111:B4) to induce sepsis and subsequently trigger ARC. To study the dose-dependent effect of LPS on the renal function, three different doses (0.75, 2.0, 5.0 μg/kg/h) were administered (two ♂ piglets/dose, one sham piglet), in combination with fluid administration (0.9% NaCl) at 6 ml/kg/h. Single boluses of renal markers, i.e., creatinine [40 mg/kg body weight (BW)], iohexol (64.7 mg/kg BW), and para-aminohippuric acid (PAH, 10 mg/kg BW) were administered intravenously to evaluate the effect of LPS on the renal function. Clinical parameters were monitored periodically. Blood sampling was performed to determine the effect on hematology, neutrophil gelatinase-associated lipocalin, and prostaglandin E2 plasma levels. All piglets that were continuously infused with LPS displayed an elevated body temperature, heart rhythm, and respiratory rate 1–3 h after start of the infusion. After infusion, considerably higher total body clearances of iohexol, creatinine, and PAH were observed, independent of the administration of LPS and/or its dose. Since also the sham piglet, receiving no LPS, demonstrated a comparable increase in renal function, the contribution of fluid administration to the development of ARC should be further evaluated.